Teacher Empowerment: A Challenge for the Twenty-First Centure - Anne-Marie de Mejía (Asociación Colombiana de Profesores de Ingles, 2016)
The term empowerment is becoming increasingly commonly used, not only in the spheres of gender studies (Leon, 1997), but also in such diverse fields as Business Management (Harari, 1993), Linguistics (Cameron et al., 1992) and more recently, in English Language Teaching (ELT), as can be seen by a section of the textbook series Amazing English (Addison Wesley, 1996) dedicated to this topic. The term itself, while proving attractive at first sight, provides challenges both for analysts and translators. While Leon (1997) maintains that the appropriate Spanish translation is empoderamiento, others have rejected this as rather unwieldly and propose terms like potenciación or apoderar which are, perhaps, more transparent terms.